Основні засади і напрями інноваційного розвитку підприємств сфери послуг - Гапоненко, С.О. (Економіка промисловості, 2013)
Розглянуто нормативно-законодавчу базу інноваційного розвитку підприємств у сфері послуг в Україні. Виділено ключові проблеми та загрозу переорієнтації вітчизняної науки на вирішення проблем інноваційного розвитку інших країн. Проведено порівняння за науково-інноваційними показниками розвитку України з деякими країнами ЄС.
Ключові слова: сфера послуг, інноваційний розвиток, країни ЄС, економічна діяльність. Рассмотрена нормативно-законодательная база инновационного развития предприятий в сфере услуг в Украине. Выделены ключевые проблемы и угроза переориентации отечественной науки на решение проблем инновационного развития других стран. Проведено сравнение по научно-инновационными показателями развития Украины с некоторыми странами ЕС.
Ключевые слова: сфера услуг, инновационное развитие, страны ЕС, экономическая деятельность. The article considers the regulatory-legislative base of innovation development of service sphere enterprises in Ukraine. The key issues and the threat of a reorientation of national science at solving the problems of innovation development of other countries are highlighted. The main causes of these problems are formed. Basic developments and programs in the state formation of innovation policy are considered as well.
The study conducted a comparison of scientific and innovation development indices in Ukraine with some EU countries. The innovation activity in the market of services in Ukraine by the volume of expenses on technological innovations, type of expenses, and economic activities of enterprises is analyzed. It also analyzed the distribution of innovation services sold by enterprises with technological innovation in terms of novelty level and economic activities.
The findings formed the main problems and directions for their solution in the innovation development of the service sphere enterprises in Ukraine.
Keywords: service sphere, innovation development, EU countries, economic activity.